The Current State of Production and Sale of Apples in Ukraine - Dudarieva, A. V. (My University, 2020)
Apple is considered a valuable crop not only in Ukraine but also in the world, and its fruits are indispensable in the diet of every person. To meet the needs of the population in these products, the efficiency of functioning and development of the domestic apple market is important. Because of this, it is quite important to study the situation, the prices, the establishment of positive and negative factors influencing the formation of this market.
Keywords: apple; fruits; market of apples